Persistence and risk factors of occult hepatitis B virus infections among antiretroviral therapy-naïve people living with HIV in Botswana - Anderson, Motswedi; Phinius, Bonolo B.; Phakedi, Basetsana K.; Mudanga, Mbatshi; Bhebhe, Lynnette N.; Tlhabano, Girlie N.; Motshosi, Patience; Ratsoma, Tsholofelo; Baruti, Kabo; Mpebe, Gorata; Choga, Wonderful T.; Marlink, Richard; et al. (Frontiers in Microbiology, 2024)
We aimed to determine the kinetics of occult hepatitis B infection (OBI) among people with HIV 34 (PWH). The study used archived plasma samples from longitudinal HIV natural history studies. We 35 identified new OBI cases, and assessed risk factors for OBI using Cox proportional hazards 36 regression analysis. At baseline, 8/382 [(2.1%) (95% CI: 1.06-4.1)] samples tested positive for 37 hepatitis B surface antigen (HBsAg + ). Of the 374 HBsAg negative samples, 76 had sufficient sample 38 volume for HBV DNA screening. OBI positivity (OBI + ) at baseline was reported in 11/76 [14.7% 39 95% CI (8.3 -24.1)] HBsAg-negative (HBsAg -) participants. Baseline HBsAg negative samples with 40 sufficient follow-up samples (n = 90) were used for analysis of newly identified OBI cases. 41 Participants contributed 129.74 person-years to the study and were followed for a median of 1.02 42 years (IQR: 1.00 -2.00). Cumulatively, there were 34 newly identified OBI cases from the 90 43 participants, giving a rate of 26.2/100 person-years (95% CI: 18.7 -36.7). Newly identified OBI 44 cases were more common among males than females (61.1% vs 31.9%), and among participants with 45 CD4 + T cell counts ≤450 cells/mL (p value = 0.02). Most newly identified OBI cases [55.9% (19/34)] 46 were possible reactivations as they were previously HBV core antibody positive. There was a high 47 rate of newly identified OBI among young PWH in Botswana especially in males and in participants 48 with lower CD4 + T cell counts. OBI screening in PWH should be considered because of the risk of 49 transmission, possible reactivation, and risk factors for the development of chronic liver disease, 50 including hepatocellular carcinoma. 51